Correlations between left ventricular rotational mechanics and parasympathetic autonomic function—results from the three-dimensional speckle-tracking echocardiographic MAGYAR-Healthy Study - Nemes, Attila (Quant Imaging Med Surg, 2021)
Left ventricular (LV) twist is calculated from the net difference of counterclockwise apical and clockwise basal rotation during systole. The current study was designed to evaluate correlations between autonomic function and LV rotational mechanics in healthy subjects. The present study comprised 18 healthy subjects (mean age: 36±12 years, 12 men). Three-dimensional speckle tracking echocardiography (3DSTE) could be used for non-invasive evaluation of LV rotation and twist. Autonomic function was assessed by means of 5 standard cardiovascular reflex tests. During 3DSTE, basal LV rotation proved to be −3.24±2.02 degree, while apical LV rotation was 9.08±3.04 degree, therefore LV twist was 11.70±6.80 degree. Valsalva test showed significant correlations with LV basal (r=0.529, P=0.019) and apical rotations (r=−0.534, P=0.022), and LV twist (r=−0.467, P=0.044). Heart rate response to deep breathing significantly correlated with LV twist, as well (r=−0.452, P=0.052). The other tests had no any relationship with rotational characteristics. Correlations exist between parasympathetic autonomic function and 3DSTE-derived LV rotation and twist in healthy subjects.